Mind the Gap: The Efficiency Convergence of ASEAN Plus Three Economies - Yasin, Mohammad Zeqi (Journal of Developing Economies, 2023)
This study aims to examine the performance of technical efficiency convergence (Beta and Sigma convergences) of 10 ASEAN economies as well as other three main partners from East Asia, namely China, South Korea, and Japan for the years of 1990-2021, and addresses the determinants of this convergence consisting of foreign direct investment (FDI), export, and import. By using Stochastic Frontier Analysis to estimate technical efficiency as well as panel dynamic of Generalized Methods of Moment (GMM) to test convergence, we found robust findings of convergence moments, both the catching up effect (Beta Convergence) as well as inequality reduction (Sigma Convergence) across the countries. The effect of FDI inflow to the growth of technical efficiency growth is positive. Coupled to this, a higher ratio of export to the GDP affects positively to the efficiency growth by about 14%-26%. In contrast, importing causes diminishing efficiency growth. The effect of FDI is significant in reducing the inequalities of efficiency only in the period of 2006-2021. While export reveals positive significance in affecting efficiency gap, import discourages efficiency gap to enlarge, indicating that import substitution remains unable to be implemented in some countries to obtain efficiency.